Strategi Visual Kosmetik Jacquelle Dalam Membangun Brand Awareness Bagi Para Cosplayer Indonesia - Edy Chandra; Vira Wilona (LPPM STIKI Malang, 2024)
A large portion of the development of the Z generation is growing, one of the portions of the Generation Z who loves cosplay. Certainly a portion of this fact provides an overview of the opportunity for Jaquelle Beaute's products to introduce the product brand to its target.(tujuan penelitian). This fact will be an attraction to research and design a visual strategy on social media Instagram. With methods of qualitative research descriptive to be able to produce creative visual ideas that can ultimately increase brand awareness of the product Jaquelle Beaute.